Implementation of a Cybergogy-Based Learning Model to Improve Learning Outcomes of Generation Z Students in the Mechanical Engineering Education Departmen - Ninik Rahayu Ashadi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The objectives of this study are to: (1) examine the implementation of the Cybergogy-based learning model in the Mechanical Engineering Education Department, particularly in the Fabrication course; and (2) analyze students’ perceptions of its application in the learning process. This research employs a descriptive quantitative approach. Rather than testing hypotheses on relationships among variables, it aims to describe the extent to which the Cybergogy model has been implemented and how students perceive its effectiveness in learning activities. The findings reveal that: (1) the implementation of the Cybergogy model was carried out through three main stages based on the 3E Framework (Engagement, Empowerment, and Enhancement) across nine instructional steps. Each stage was evaluated in terms of student engagement, collaborative activities, and learning outcomes using observation sheets, questionnaires, and learning achievement tests. (2) Students’ perceptions of the Cybergogy-based learning model were assessed through three dimensions: (a) digital learning engagement, (b) learning autonomy (empowerment), and (c) learning improvement and satisfaction (enhancement), with an average score of 4.28. Based on the results, it can be concluded that: (1) the overall average score of 4.24 indicates that the implementation of the Cybergogy learning model falls into the good to very good category; and (2) students’ perceptions of the Cybergogy-based learning model are highly positive. Most students reported that learning became more flexible, collaborative, and motivating, encouraging them to engage in more independent learning.